Scientific basis and method to set up the map of zonation area for sweeping flood - Tu, Tran Van (Vietnam Journal of Earth Sciences, 2012)
Flash flood zonation is an effective forecasting solution to prevent and mitigate damage. This is a new type of natural disaster in Vietnam and there is not similar study completed on over the world. This paper presents the basis of scientific and criteria for forecasting flash flood mapping in small and medium scales rate (1:50,000 or less). However, it can be used to map larger scale, to service design and forecasts for each project or medium and small basins. Flash flood forecasting is a very important task in the stage of prevention and mitigation. The formation and development of flash flood depend on two basic conditions: water and buffer. In forecast mapping, the main water source is considered from rain. Thus, rain intensity is very important parameter for forecasting map. Today frequency from 1% to 5% of the day weather rain gauge is to be used. The buffer factors on map include slope, condition of vegetation and soil by different ratios. Flash flood forecasting maps can be established by factor analysis which is used by the empirical formula of hydrological study for basin. The weights of formula were determined on the basis of coefficients or exponents of the components. However, the types of flash flood such as complex flood and the debris flood can not be determined from the factor analysis. They formed separately and depend on the particular geography. The intensity and frequency of complex flood and debris flood for each points can be established. Author hopes this study may be open to managers and professional studies supplementary to the task of mapping/zoning flash flood completely.Đọc ngữ âm